A comparison of national essential medicines lists in the Americas - Liane Steiner; Darshanand Maraj; Hannah Woods; Jordan Jarvis; Hannah Yaphe; Itunu Adekoya; Anjli Bali; Nav Persaud (Pan American Health Organization, 2020)
Objectives. To compare national essential medicines lists (NEMLs) from countries in the Region of the Americas and to identify potential opportunities for improving those lists. Methods. In June of 2017, NEMLs from 31 countries in the Americas were abstracted from documents included in a World Health Organization (WHO) repository. The lists from the Americas were compared to each other and to NEMLs from outside of the Americas, as well as with the WHO Model List of Essential Medicines, 20th edition ("WHO Model List") and the list of the Pan American Health Organization (PAHO) Regional Revolving Fund for Strategic Public Health Supplies ("Strategic Fund"). Results. The number of differences between the NEMLs from the Americas and the WHO Model List were similar within those countries (median: 295; interquartile range (IQR): 265 to 347). The NEMLs from the Americas were generally similar to each other. While the NEMLs from the Americas coincided well with the Strategic Fund list, some medicines were not included on any of those NEMLs. All the NEMLs in the Americas included some medicines that were withdrawn due to adverse effects by a national regulatory body (median: 8 withdrawn medicines per NEML; IQR: 4 to 12). Conclusions. The NEMLs in the Americas were fairly similar to each other and to the WHO Model List and the Strategic Fund list. However, some areas of treatment and some specific medicines were identified that the countries should reassess when revising their NEMLs.